DIAGNOSIS AND MANAGEMENT OF KATISHOOLA (LOW BACK PAIN) IN AYURVEDA: A CRITICAL REVIEW (AYUSHDHARA, 2017)
Low back pain (LBP) is an important clinical, social, economic, and public health problem affecting the population indiscriminately. It is a disorder with many possible etiologies, occurring in many groups of the population, and with many definitions. Consequently, the vast literature available on LBP is not only heterogeneous but also contradictory. A clear description regarding the Samprapti, Lakshana of Kati Graha is explained by the Shodhala in the Kayachikitsa Khanda, Vataroga Adhikara. He has described various formulations for Kati Shoola and has specifically indicated Trayodashanga Guggulu for Kati Graha. The prevalence of LBP in Indian population has been found to vary between 6.2% (in general population) to 92% (in construction workers). Low back pain can be medically and economically devastating and is the number one cause for disability in patients younger than forty-five years of age and number three cause for disability in patients older than forty-five years of age. This problem, supposedly has a favourable natural history, although it can be remarkably disabling, has challenged the health care providers. Understanding the role of different medical systems in the management of backache is important for the cost-effective management of the disease. Physician treating backache patients should understand this, so that they can co-ordinate and integrate functionally based programs, because no single medication, modality, exercise regimen or other treatment technique may result in low backache recovery. Here in this article, the diagnostic and treatment aspects are discussed critically using Ayurvedic and modern literatures.